(untitled) (Psychology Travelogs, 2023)
The article is devoted to the study of the effectiveness of socio-pedagogical and psychological measures and ways of organizing a safe educational environment aimed at the prevention of mobbing, as a manifestation of a violent way of communication among teenagers. The author revealed the essence of the concepts «psychological health», «prevention», types of prevention, «psychological safety». The implementation of preventive programs aimed at preventing mobbing and other types of harassment acts as a necessary tool for prevention, overcoming the exacerbation of conflicts, their negative consequences and will allow creating a safe environment in the educational space of children and adolescents. Types of prevention are described, among which, primary - aimed at preventing the occurrence of a problem; secondary - to prevent the aggravation of the problem and its consequences; tertiary or rehabilitation - work carried out with persons affected by the problem and aimed at preventing its recurrence. In the social aspect, the psychological safety of the environment is understood as the state of the environment, free from manifestations of psychological violence in the process of human interaction, which contributes to the sat-isfaction of the basic needs in personal and trustful communication, creates the referential significance of the environment, ensures the mental health and psychological security of everyone, the psychological safety of the individual. For the educational environment, it is important to emphasize the restoration of relations between the participants in the conflict and the creation of a friendly atmosphere that will facilitate learning. Educational work among teachers regarding the forms and methods of preventive education, age characteristics of students, the formation of antisocial, deviant behavior by involving them in active participation in debates, trainings, educational seminars is an important component of ensuring preventive work in educational institutions.